Cognitive changes after methanol exposure: Longitudinal perspective - Bukacova, Katerina; Mana, Josef; Klempíř, Jiří; Ryšánková, Irena; Brožová, Hana; Poláková, Kamila; Žák, Ivan; Pelclová, Daniela; Zakharov, Sergey; Růžička, Evžen; Bezdicek, Ondrej (Toxicology letters, 2021)
BACKGROUND: From 2012 to 2013, there was a mass methanol poisoning outbreak in the Czech Republic. Methanol metabolites can cause specific lesions in the basal ganglia, subcortical white matter, and optic nerve. However, long-term sequelae of methanol poisoning on cognitive functioning have not yet been explored. The current study aimed to delineate the cognitive changes observed in methanol poisoning survivors in the seven years since 2012. METHODS: We conducted longitudinal research with repeated measurements in 2013, 2015, 2017 and 2019 to evaluate the development of cognitive changes after acute methanol poisoning. A complex neuropsychological battery consisted of tests of global cognitive performance, auditory and visual attention, executive functioning, learning and memory, working memory and language. Motor performance measures and depression scale were also included. RESULTS: Repeated measures ANOVA of four measurements with post-hoc tests showed a significant decline in the Mini-Mental State Examination (p = 0.007); however, other parameters were not significantly decreasing. In comparison to normative values, the z-scores for each test measure, in the memory domain, in particular, ranged from 43 to 60 % of participants below 1.5 SD. Mild to severe depression levels from the onset of poisoning improved during the seven years, returning to normal in up to 27 % of participants. CONCLUSION: In the longitudinal perspective, methanol poisoning survivors manifest progressive global cognitive decline and overall persistent below-average cognitive performance with some improvements in the frequency of depressive symptoms.
Keywords: mladý dospělý; Cognitive Dysfunction; Memory, Episodic; Humans; lidé; Prevalence; deprese; Czech Republic; lidé středního věku; Depression; methanol; neuropsychologické testy; prevalence; Time Factors; Middle Aged; longitudinální studie; časové faktory; Female; Male; kognice; Adult; Memory Disorders; kognitivní dysfunkce; poruchy paměti; Longitudinal Studies; Methanol; Neurotoxicity Syndromes; mužské pohlaví; Aged; ženské pohlaví; neurotoxické syndromy; Young Adult; epizodická paměť; dospělí; Neuropsychological Tests; Česká republika; Cognition; senioři